The Influence Of The Implementation Of Educational Supervision By The Principal On Teacher Performance In Schools - Yudhie Suchyadi; Nurjanah Nurjanah (JURNAL MANAJEMEN PENDIDIKAN, 2022)
This study aims to determine and clarify how the effect of the implementation of educational supervision by the principal on the performance of teachers in schools. Conducting research using one approach, namely a quantitative approach and expost facto type. Teachers in schools became the subject of research by taking a sample of 25 teachers, using proportional random sampling technique, and using a questionnaire about the implementation of educational supervision by the principal and data on the results of teacher performance assessments owned by the school. This research and assessment can be seen that the implementation of educational supervision by the principal does not have a positive effect on teacher performance and the implementation of educational supervision by the principal has a weak or even very weak effect on the performance of teachers in schools.